Development of educational multimedia to improve the understanding of nature conservation: A study of Gunung Gede Pangrango National Park’s conservation volunteers - Ika Rosmalasari; Rita Retnowati; Herfina Herfina (Universitas Pakuan, 2020)
The purpose of this research is to develop a multimedia conservation of education application, and to determine its effectiveness in understanding the nature conservation of conservation cadres or volunteers in the national park area. This research used the Research and Development method of the model Borg Gall which was modified into five stages, were Research and Information Collecting, Planning, Developing Preliminary of Product, Preliminary Field Testing and Main Product Revision. While the application development stage used the SDLC (System Development Life Cycle) method which consisted of planning, analysis, design, implementation and testing stages. Data obtained from the validation of material experts and multimedia experts. The effectiveness test used the analysis of the N-Gain value of each indicator of the pretest and posttest questions. To develop educational multimedia applications need to analysis, preparing the designs and materials, developing the application, validating applications by experts, assessing the quality of application systems, small and large scaling field trials and evaluation. The purpose research product is the digital information entitled E-Info of Nature Conservation Media which can be accessed free of charge via the link (ika.gedepangrango.org). According to data analysis we concluded that the development of educational multimedia applications can increase understanding of nature conservation for conservation volunteers in the national park area. The Scores pretest and posttest obtained an average N-Gain score of 0.73 and a percentage score of 73.33% with the criteria ``High